A relação entre a atuação do Estado islâmico e a securitização da política migratória estadunidense: o caso dos imigrantes muçulmanos - Cardoso, Anna Karollinne Lopes (2019)
This dissertation discusses the influence of the Islamic State on US immigration policy during the Trump Government and has as its general objective to demonstrate how the terrorist organization "Islamic State" (IS) has impacted on the selection process of individuals seeking into the United States. To do so, the concept of securitization of the Copenhagen School is used to analyze the selection of immigrants practiced during the first 100 days of Donald Trump's administration. It is argued, therefore, that although the securitization of borders is common to the United States, the process of securitization of individuals of Muslim origin is due to the rise of the IS. In order to verify this assumption and to reach the general objective of the research, one starts from the historical interpretation of the American migratory policies. For the purposes of this research, it is understood that migration is part of the State policy and that each Government changes it according to their interests and the scenario in which they are inserted. In this way, legislative texts produced on the subject are used, demonstrating the speech produced by the leader and the position adopted by the State. Next, it is the American migratory policy. Similarly, the emergence and strengthening of the IS and its relationship with the United States is addressed. Finally, it seeks to demonstrate how the terrorist acts operated by the Islamic State influenced the migratory flow, associating migrants with terrorists and leading to the intensification of the securitization of borders.